Eighteen-level inverter control with minimum switching losses - Abdul Kadir, M.N.; Mekhilef, Saad (2009)
A multilevel multistage inverter design and its corresponding control strategy are presented. The hybrid inverter has a high voltage stage composed of the six-switch conventional three phase inverter with its outputs connected in series to the outputs of three-level H-bridge medium and low voltage stages. The voltage ratio has been selected to form 18-level provide maximum number of uniform steps. The suggested control strategy has been developed to ensure minimum switching losses focusing on holding the higher voltage stage state as long as it is feasible. The reference voltage vector has been approximated to the nearest inverter voltage vector. A special definition of state zone has been introduced for the low voltage stage to enable the achievement of the reference vector with minimum error. The proposed control strategy has been tested and its short computational time and low memory requirement has been proven.